Design, synthesis, crystal structure and in vitro cytotoxic properties of a novel Schiff base derived from indole and biphenyl. Issue 7 (23rd June 2017) - Bu, Fan-Zhi; Tan, Xue-Jie; Xing, Dian-Xiang; Wang, Chao
Abstract : A novel Schiff base derived from indole and biphenyl has been designed, synthesized and fully characterized. Molecular docking indicated a good dihydroorotate dehydrogenase (DHODH) inhibitory activity and in vitro inhibition evaluation against lung and breast cancer cell growth proved the prediction. Abstract : A novel and potentially active dihydroorotate dehydrogenase (DHODH) inhibitor, namely 3‐({( E )‐[( E )‐1‐(biphenyl‐4‐yl)ethylidene]hydrazinylidene}methyl)‐1 H ‐indole (BEHI) acetonitrile disolvate, C23 H19 N3 ·2CH3 CN, has been designed and synthesized. The structure of BEHI was characterized by elemental analysis, Q‐TOF (quadrupole time‐of‐flight) MS, NMR, UV–Vis and single‐crystal X‐ray diffraction. The antitumour activity of the target molecule was evaluated by the MTT method. Results indicated that BEHI exhibited rather potent cytotoxic activity against human A549 (IC50 = 20.5 µ M ) and mouse breast 4T1 (IC50 = 18.5 µ M ) cancer cell lines. Meanwhile, to rationalize its potencies in the target, BEHI was docked into DHODH and the interactions with the active site residues were analyzed. Single‐crystal structure analysis indicated that hydrogen bonds are present only between BEHI and acetonitrile solvent molecules in the asymmetric unit. The interplay of weak π–π stacking and weak C(N)—H…π interactions between neighbouring BEHI molecules play crucial roles in the formation of the final supramolecular frameworks.